2019
DOI: 10.1021/acs.jafc.8b05814
|View full text |Cite
|
Sign up to set email alerts
|

Jaboticabin and Related Polyphenols from Jaboticaba (Myrciaria cauliflora) with Anti-inflammatory Activity for Chronic Obstructive Pulmonary Disease

Abstract: Myrciaria cauliflora (jaboticaba) is an edible fruit common in Brazil that has been used for treating respiratory diseases, including chronic tonsillitis and asthma. This study explores the distribution of an anti-inflammatory depside, jaboticabin, in different parts of the jaboticaba plant as well as major polyphenols from the wood of jaboticaba, some with biological activity similar to jaboticabin. The peel of the fruit was found to be the major source of jaboticabin. This is the first phytochemical study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
0
14
0
4
Order By: Relevance
“…Andrographolide (Tan et al, 2015;Tan et al, 2018), elfinidina-3-glucosídeo, cianidina-3-glucosídeo, delfinidina, e cianidina (Flores et al, 2012), Silimarina (Li et al, 2014), kuwanon E, kuwanon G e norartocarpanona (Lim et al, 2013), jaboticabino (Zhao et al, 2019), Silibinina (Park et al, 2016), Bixina (Zhang et al, 2018), Morina (Cai et al, 2018), Eucalipitol (Kennedy-Feitosa et al, 2020, resveratrol oligômeros Suffruticosol A (Ryu et al, 2015), Baicalina (Lixuan et al, 2010) e S-Pentasina (Shih et al, 2011) foram os que apresentaram eficácia no tratamento experimental de doenças respiratórias crônicas.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Andrographolide (Tan et al, 2015;Tan et al, 2018), elfinidina-3-glucosídeo, cianidina-3-glucosídeo, delfinidina, e cianidina (Flores et al, 2012), Silimarina (Li et al, 2014), kuwanon E, kuwanon G e norartocarpanona (Lim et al, 2013), jaboticabino (Zhao et al, 2019), Silibinina (Park et al, 2016), Bixina (Zhang et al, 2018), Morina (Cai et al, 2018), Eucalipitol (Kennedy-Feitosa et al, 2020, resveratrol oligômeros Suffruticosol A (Ryu et al, 2015), Baicalina (Lixuan et al, 2010) e S-Pentasina (Shih et al, 2011) foram os que apresentaram eficácia no tratamento experimental de doenças respiratórias crônicas.…”
Section: Resultsunclassified
“…Compostos como o Revesratrol e a Bixina inibem o TGF-β (Chen et al, 2016,;Zhang et al, 2018); os polissacarídeos de Astragulus, C. pilosula e D. officinale inibem a produção de citocinas Interleucina -6 e -8 (IL-6 e -8) (Chu et al, 2016;Song et al, 2016) bem como outros metabolitos secundários (Flores et al, 2012;Kim et al, 2017;Zhao et al, 2019); Fortisiasida , Timosaponina A-III e Morina inibem a Interleucina 1β (Cheng et al, 2015;Cai et al, 2018;Park et al, 2018); Platicodina D (Gao et al, 2017), Stemonina (Zhang et al, 2017) e Tuberstemonia N (Jung et al 2015) apresentaram atividade inibitória do fator de necrose tumoral α (TNF-α).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…In recent years, with the in‐depth study of flavonoids, it was found that Alpinetin had antibacterial, antioxidant, anticancer, antithrombotic, hypotensive, hypolipidemic, hypoglycemic, antiemetic, and analgesic effects (Liu et al., 2019; Zhao et al., 2018; Zhao et al., 2018). At the same time, other flavonoids had been found to play a positive role in improving COPD (Bao et al., 2013; Zhao et al., 2019). However, the effect of Alpinetin on COPD is relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid and ellagic acid (and their derivatives) are usually found in fruits and other plant-derived products [55,58] with antioxidant activity, including those from Myrciaria genus [59,60]. Furthermore, some works have reported that these compounds are potent anti-inflammatory, analgesic, and neuroprotective agents [60][61][62].…”
Section: Hplc Analysis Of the Acetone Extract Of M Floribundamentioning
confidence: 99%